An inflammatory T-cell-stromal axis contributes to hematopoietic stem/progenitor cell failure and clonal evolution in human myelodysplastic syndrome - Chen, Lanpeng; Bian, Yujie; Pronk, Eline; van Dijk, Claire; V.D. van Tienhoven, Tim; Hoogenboezem, Remco M.; Bindels, Eric M.; Bosch, Dennis; Fazeli, Sadaf; de Graaf, Aniek O.; Westers, Theresia M.; Kholmatov, Maksim; et al. (Nature communications, 2025)
Myelodysplastic syndrome (MDS) is characterized by bone marrow failure, clonal evolution and leukemic progression, but the pathophysiologic processes driving these events remain incompletely understood. Here, by establishing a comprehensive single-cell transcriptional taxonomy of human MDS, we reveal that inflammatory remodeling of bone marrow stromal niches is a common early feature, irrespective of the genetic driver landscape. We identify an activated CD8-T-cell subset as a source of stromal inflammation via TNF-receptor signaling, which prompts the inflammatory rewiring and loss of repopulating ability of residual normal hematopoietic stem/progenitor cells (HSPC). Mutant HSPCs display relative resistance to this inflammatory stress and reside predominantly in a transcriptional ‘high output’ state, providing a biological framework to their competitive advantage in an inflammatory microenvironment. Consistent with this, stromal inflammation associates with leukemic progression and reduced survival. Our data thus support a model of immune-stromal inflammatory signaling driving tissue failure and clonal evolution in the hematopoietic system. Mechanisms of clonal evolution in myeloid neoplasms remain incompletely understood. Darwinian theory predicts that the (micro)environment of clone-propagating stem cells may contribute to clonal selection. Here, we provide data fitting this model, establishing a relationship between stromal niche inflammation, inflammatory stress in HSPCs, clonal resistance and leukemic evolution in human MDS. Mechanisms of clonal evolution in myeloid neoplasms remain incompletely understood. Darwinian theory predicts that the (micro)environment of clone-propagating stem cells may contribute to clonal selection. Here, authors provide data fitting this model, establishing a relationship between stromal niche inflammation, inflammatory stress in HSPCs, clonal resistance and leukemic evolution in human myelodysplastic syndrome.